Magnetohydrodynamic simulation and test of compression arc-extinguishing device under icing condition - Ping Huang; Shijie Xu; Honglin Qin; Guoting Yang; Junlin Huang; Zhihao Li (AIP Advances, 2024)
When the weather is cold and wet, the insulator and the transmission line components often undergo icing. In order to study the inhibition effect of the compression arc-extinguishing device with icing on the recovery of arc plasma conductivity and air disruptive strength, this paper will verify it through simulation and test. In the simulation part, a two-dimensional geometric model is established, and the magnetohydrodynamic equation group is used as the control equation group. The breakdown characteristics of the device with and without icing are compared, and the dynamic characteristics of the arc are studied in terms of temperature and conductivity. The results show that the temperature of the arc plasma can be reduced to 3000 K within 1 ms, and the conductivity can be reduced to 0 within 250 µs. In the test part, the suppression effect on arc current amplitude after the device with icing is subjected to high current impact is verified, and the coupling triggering method of impulse voltage and power frequency voltage is adopted to further verify the arc extinguishing condition of the device when the power frequency current continues. The results show that the amplitude of the arc produced by high current impulse decreases from 67 to 35 kA and to 0 within 1 ms after passing through the device with icing, and the current amplitude can still drop to 0 at 2.5 ms after adding the power frequency voltage. It is proved that the device with icing can inhibit the recovery of arc plasma conductivity and air disruptive strength.